2016
DOI: 10.1016/j.tmp.2016.09.004
|View full text |Cite
|
Sign up to set email alerts
|

The dynamics of travel avoidance: The case of Ebola in the U.S.

Abstract: 2016-11-03T14:11:40

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
259
4
8

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 302 publications
(314 citation statements)
references
References 85 publications
10
259
4
8
Order By: Relevance
“…Results of an online survey carried out by Jones and Salathe (2009) during the beginning of the swine flu outbreak explained that older age was linked with more avoidance behaviors including the avoidance of large gatherings, and public transport. Cahyanto et al (2016) conducted an online survey to study the factors influencing the avoidance of domestic travels by Americans due to the confirmed Ebola virus cases. They concluded that perceived vulnerability, perceived risk, subjective knowledge, and self-efficacy affect the avoidance of domestic travel significantly.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Results of an online survey carried out by Jones and Salathe (2009) during the beginning of the swine flu outbreak explained that older age was linked with more avoidance behaviors including the avoidance of large gatherings, and public transport. Cahyanto et al (2016) conducted an online survey to study the factors influencing the avoidance of domestic travels by Americans due to the confirmed Ebola virus cases. They concluded that perceived vulnerability, perceived risk, subjective knowledge, and self-efficacy affect the avoidance of domestic travel significantly.…”
Section: Related Workmentioning
confidence: 99%
“…Fear of infection and perceived risk also significantly influence travel behaviors, particularly for transit use, and the influence varied based on the infected area and demographic characteristics of the people ( Kim et al, 2017 , Cahyanto et al, 2016 ). During pandemics, people perceive a higher risk for all types of trip types and avoid traveling to places where they perceive medium to high risk ( Hotle et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…For example, during the COVID-19 outbreak, people who had higher outcome expectations about engaging in avoidant behaviors were more likely to follow the recommended guidelines [ 61 ]. Assessments about self-efficacy also positively impacted intentions to self-isolate during COVID-19, and influenced Americans’ avoidance of domestic travel during the Ebola outbreak [ 62 , 63 ]. During the Influenza A (H1N1) crisis, high levels of assessments about one’s self-efficacy were associated with more statements from participants that they would take avoidance measures [ 64 ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Additionally, an elevated health-related risk is normally associated with perceptual and behavioral changes (Witte et al 1996). Information seeking can be regarded as one of the behavioral manifestations of one's RPAs, both in a general public health context (Rimal and Real 2003) and in a tourism context (Cahyanto et al 2016). Tourists may engage in information search as a way to protect themselves against risk, as well as to reduce uncertainty (Cahyanto et al 2016).…”
Section: Information Search Behavior In Risk and Crisis Communicationmentioning
confidence: 99%